2020
DOI: 10.1021/acssuschemeng.0c01429
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Continuous Flow Metal–Organic Framework (MOF) Synthesis Using Supercritical CO2

Abstract: The high surface areas and tunable porous structures of Metal−Organic Framework (MOF) materials offer desirable capabilities in a wide range of applications. One challenge to the widespread use of MOFs is a lack of large-scale manufacturing synthesis processes. This paper presents a novel method of continuous synthesis of MOF using supercritical carbon dioxide (scCO 2 ), introduced through a custom counter-current mixer, to provide enhanced heat and mass transfer to MOF precursor materials. The method was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 78 publications
0
21
0
Order By: Relevance
“…The use of flow chemistry to achieve product intensification by improving heat and mass transfer, decreasing the use of solvents, and improving scalability through parallelization has transformed many disciplines, including polymer chemistry, organic synthesis, and photochemistry . Numerous studies over the past decade have demonstrated the feasibility of synthesizing MOFs in flow; however, the influence of synthetic parameters on product crystallinity and scale-up strategies for high-throughput manufacturing by considering transport processes have not been explored thoroughly. Here, we investigate the use of flow reactors for the accelerated synthesis of Ni 2 Cl 2 (BTDD) under mild solvothermal conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The use of flow chemistry to achieve product intensification by improving heat and mass transfer, decreasing the use of solvents, and improving scalability through parallelization has transformed many disciplines, including polymer chemistry, organic synthesis, and photochemistry . Numerous studies over the past decade have demonstrated the feasibility of synthesizing MOFs in flow; however, the influence of synthetic parameters on product crystallinity and scale-up strategies for high-throughput manufacturing by considering transport processes have not been explored thoroughly. Here, we investigate the use of flow reactors for the accelerated synthesis of Ni 2 Cl 2 (BTDD) under mild solvothermal conditions.…”
Section: Introductionmentioning
confidence: 99%
“…33 To this end, we surmised that switching the synthesis of MOF-808 from batch to flow would improve our understanding of early stage crystallization processes as well as provide an alternative low-cost and high-throughput route to match industrial-scale production at competitive market prices. 34,35 Numerous studies over the past few years have demonstrated the benefits of synthesizing MOFs in flow, [36][37][38][39][40][41][42][43][44] however, the influence of synthetic parameters on product crystallinity and scale-up strategies for high-throughput manufacturing have not been explored thoroughly. Only a handful of studies 37,45 have established the feasibility of synthesizing MOF-808 in flow, but a comprehensive understanding on the influence of synthetic parameters on product crystallinity, pathways to achieve high process yields, and solvent use optimization have not been explored in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the mixing section length is defined as the distance from the end of the inner inlet pipe to the reactor section pipe's centerline as commonly done in counter current mixing sections. 29 The volume for the flow in the reactor section was defined by the inner diameter of the reactor section pipe and the length of the reactor section. The density of the fluid in the mixing and reactor sections was defined from NIST RefProp at the isobaric pressure of 23.5 MPa and using the thermocouple data, T5, for the temperature of the colloidal solution exiting the mixing section.…”
Section: Flow Characterizationmentioning
confidence: 99%